Waste to Biofuel Technology : Future Energy - Anish, Khan (Springer Nature Singapore Pte Ltd, 2024)
This book gives an overview of the latest technologies in the conversion of wastes products to biofuel or chemicals which are more eco-friendly and sustainable as compared to the ordinary petroleum derivatives. It describes a variety of technology such as combustion, gasification, paralysis, anaerobic digestion, and fermentation, which are used in the processing of solid/liquid waste produced by the different residential and industrial sectors into more economically useful by-products. The content of this book resonates with researchers, industrial practitioners, and government policymakers who are looking into developing more sustainable practices in dealing with waste products and looking into waste to energy technologies.